ANALYSIS OF INDUSTRIAL ENTERPRISES INNOVATIVE ACTIVITY OF UKRAINE IN THE CONTEXT OF INNOVATIVE PROJECTS SUCCESSFUL IMPLEMENTATION - CHAIKOVSKA, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study identifies Ukraine’s place in the Global Innovation Index for the period 2016-2021. In 2016, Ukraine ranked 56th, in 2017 - 50, in 2018 - 43, in 2019 - 47, in 2020 - 45 and in 2021 - 49, which indicates the deterioration of Ukraine’s position in 2021. It was revealed that the strengths of Ukraine are the results of knowledge and technology; human capital and research, and the weaknesses are institutions and infrastructure. The paper analyzes the innovative activity of industrial enterprises of Ukraine in the period 2016 - 2020 in the context of successful implementation of innovative projects. It was found that the share of the number of industrial enterprises that implemented innovations, ie to implement innovative projects (products and / or technological processes) in the total number of industrial enterprises was the highest in 2016 and amounted to 16.6%. The growth rate of the share of industrial enterprises that implemented innovations in 2017 compared to 2016 is -13.86%; 2018 to 2017 - 9.09%; 2019 to 2018 - - 1.54%; 2020 (preliminary data) to 2019 - 7.97%. Among the introduced types of innovative products (goods, services) by industrial enterprises of Ukraine in the period 2016 - 2020, 23.63% are new for the market in 2016; in 2017 - 19.98%; in 2018 - 25.19%; in 2019 - 19.46% and in 2020 (preliminary data) - 16.99%. In 2020, there is the lowest share of new types of innovative products (goods, services) introduced to the market in their total number. The highest level of expenditures on innovation is observed in 2016 and amounts to UAH 23,229.5 million, in 2017 there is a significant decline to the level of UAH 9,117.5 million. In 2018-2020, there is a moderate increase in spending on innovation, but their level is much lower than in 2016. In the structure of innovation costs of industrial enterprises of Ukraine, GDR occupies in 2016 - 10.6%, in 2017 - 23.8%, in 2018 - 26.3%, in 2019 - 20.5%, and in 2020 - 24.2% (preliminary data), which reflects their insignificant level. The main share among the sources of financing of innovation is the own funds of enterprises, the funds of non-resident investors do not exceed 1.2% of the total cost of innovation. It is established that the successful implementation of innovative projects of enterprises depends on optimal project management and knowledge management in the enterprise in their systematic combination, which will intensify innovation to increase market value of the enterprise and strengthen competitive positions.